The Hahn Sequence Space of Fuzzy Numbers Defined by a Modulus Function - A. Pandiarani (International Journal of Mathematics And its Applications, 2016)
In this article we introduce new sequence spaces h(F,f),h_∞(F,f) and h_p (F,f,s) of sequence of fuzzy numbers defined by a modulus function. Further some inclusion relations regarding these spaces are studied.